2018
DOI: 10.1096/fj.201800636r
|View full text |Cite
|
Sign up to set email alerts
|

Lack of acute xenogeneic graft‐versus‐host disease, but retention of T‐cell function following engraftment of human peripheral blood mononuclear cells in NSG mice deficient in MHC class I and II expression

Abstract: Immunodeficient mice engrafted with human peripheral blood mononuclear cells (PBMCs) support preclinical studies of human pathogens, allograft rejection, and human T‐cell function. However, a major limitation of PBMC engraftment is development of acute xenogeneic graft‐versus‐host disease (GVHD) due to human T‐cell recognition of murine major histocompatibility complex (MHC). To address this, we created 2 NOD‐scid IL‐2 receptor subunit γ (IL2rg)null (NSG) strains that lack murine MHC class I and II [NSG–β‐2‐mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 56 publications
7
153
0
Order By: Relevance
“…The NSG-β2m −/− mouse lacks expression of beta-2 microglobulin (β2m), eliminating murine MHC class I and resulting in the delayed development of GvHD in PBMC humanized mice. This advantage was highlighted in a recent study which observed a significant survival advantage in NSG-β2m −/− mice injected with human PBMC when compared to the parental NSG line (1). To our knowledge, this is the first study to utilize the NSG-β2m −/− PBMC model in the investigation of immunotherapeutic modulation of a human anti-tumor response.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The NSG-β2m −/− mouse lacks expression of beta-2 microglobulin (β2m), eliminating murine MHC class I and resulting in the delayed development of GvHD in PBMC humanized mice. This advantage was highlighted in a recent study which observed a significant survival advantage in NSG-β2m −/− mice injected with human PBMC when compared to the parental NSG line (1). To our knowledge, this is the first study to utilize the NSG-β2m −/− PBMC model in the investigation of immunotherapeutic modulation of a human anti-tumor response.…”
Section: Introductionmentioning
confidence: 88%
“…Host Disease (GvHD), the kinetics of which limits the duration of study and interpretation of results. Several variants of these parental mouse strains have eliminated murine MHC class I and/or II and exhibit delayed development of GvHD in the PBMC model (1)(2)(3)(4)(5). Due to their recent development, few immunotherapeutic studies have utilized these novel lines, and while limitations exist, delayed development of GvHD enables more complete characterization of immunotherapeutic modulation of the human anti-tumor response.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, this cytokine is acting on donor human effector T cells as host murine leukocytes in NSG mice do not express functional IL-2 receptors because of the absence of the IL-2 receptor c chain, 30 and since either donor human CD4 + or CD8 + T cells are sufficient to mediate GVHD in humanized NSG mice. 27,31,32 Consistent with this, the administration of low-dose IL-2 in allogeneic and humanized mouse models of GVHD results in the activation of donor effector T cells, 33,34 which circumvent any potential clinical benefits imparted by the expanded Treg cell population in these mice. 34 Notably, the co-administration of IL-10 with IL-2 can limit the expansion of effector T cells and increases survival in humanized mice with GVHD.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, 4 weeks after the AT of PBMCs, we observed equal infiltration of T cells in both autologous and allogeneic conditions ( Figure 2D), suggesting mice were at the early stage of graft-versus-host disease. The use of NSG mice that lack the murine MHC allowing to evade graft-versus-host disease but that retain T cell function upon engraftment will likely help to overcome this issue (Brehm et al, 2018). Our results also provide the first evidence that hiPSC-derived MPCs, unlike hiPSCs, are not the target of NK cells in vivo.…”
Section: Unfortunately the Low Level Of Infiltrating T Cells Preventmentioning
confidence: 75%